Salinarimonas soli sp. nov., isolated from soil. Issue 2 (28th February 2022) - Jin, Chun-Zhi; Jin, Long; Liu, Min-Jiao; Kang, Min-Kyoung; Park, So Hee; Park, Dong-Jin; Kim, Chang-Jin
Abstract : A light pink coloured bacterium, designated strain BN140002 T, was isolated from a soil sample collected in Goesan-gun, Chungcheongbuk-do, Republic of Korea. Cells of strain BN140002 T were Gram-stain-negative, aerobic, motile and rod-shaped. Phylogenetic analysis based on 16S rRNA gene sequences showed 94.7, 94.7, 93.9, 93.3, 93.4 and 93.0% similarities to Salinarimonas rosea KCTC 22346 T, Salinarimonas ramus DSM 22962 T, Saliniramus fredricksonii HL-109 T, Microvirga soli R491 T, Chelatococcus caeni EBR-4-1 T and Chelatococcus composti PC-2 T, respectively. The major polar lipids were diphosphatidylglycerol, phosphatidylglycerol, phosphatidylcholine and phosphatidylethanolamine. The major cellular fatty acids were summed feature 8 (C18 : 1 ω 7 c and/or C18 : 1 ω 6c) and summed feature 1 (C12 : 0 aldehyde and/or unknown 10.98) and the predominant ubiquinone was Q-10. The genomic DNA G+C content of strain BN140002 T was 70.1 mol%. The genomic orthoANI values between strain BN140002 T and Salinarimonas rosea KCTC 22346 T and Salinarimonas ramus DSM 22962 T were 75.0 and 74.8 %, respectively. Strain BN140002 T had a class I-C type CRISPR-Cas system (CRISPR-associated helicase Cas3, CRISPR-associated protein Cas8c, CRISPR-associated protein Cas7, CRISPR-associated RecB family exonuclease Cas4, CRISPR-associated protein 1, 2). Based on phenotypic, chemotaxonomic and phylogenetic data, strain BN140002 T should be assigned as a novel species of the genus Salinarimonas, for which the name Salinarimonas soli sp. nov. is proposed. The type strain is BN140002 T (=KCTC 42643 T =CCTCC AB 2017173 T ).